Russia’s war with Ukraine is to acquire military industrial capability and human resources - Jokull Johannesson (Journal of International Studies)
The Russia-Ukraine war presents a serious challenge as to understanding of President Putin’s geopolitical intentions. This article uses a resource dependence perspective to explain Russia’s motives for invading Ukraine. The invasion is driven by Russia’s resource gaps in military-industrial capacity and human resources, and the fact that these resource gaps could be substantially mitigated by control over Ukraine’s resources. The findings suggest implications for further research, policy and international business developments.